Phenomenology of Positive Experiences of Married People on Marital Satisfaction during Covid-19 Pandemic - Hosseinpour, Sima; Gholamzaedh Jofreh, Maryam (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study was done to analyze the positive experiences of married people on marital satisfaction during the Covid-19 pandemic in Ahvaz. Method: The research methodology was qualitative and phenomenological. A total of 20 Participants (saturated number) from married people were selected by purposeful sampling method. The semi-structured interviews were conducted with the participants. For the validity of the findings from the point of view of the experts, and for the reliability, the coding agreement coefficient was used, and its value was 0.92. Results: According to the results of thematic analysis, these themes were obtained: emotional intimacy and closeness between spouses, spouses’ pastime and joint activities, the ability of spouses to adapt and cope with new experiences positively and positive encounters with new experiences, and opportunities for skills training. Conclusion: According to the study results, it can be seen that the Covid-19 pandemic in addition to negative aspects, has positive impacts and wide-ranging effects and consequences on marital relationships in various fields.